2020
DOI: 10.1002/adfm.202001832
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polysulfamide Drug Nanogels with Microwave Augmented Tumor Accumulation and On‐Demand Drug Release for Enhanced Cancer Therapy

Abstract: Zwitterionic polymers demonstrate as a class of antifouling materials with long blood circulation in living subjects. Despite extensive research on their antifouling abilities, the responsive zwitterionic polymers that can change their properties by mild outside signals are poorly explored. Herein, a sulfamide‐based zwitterionic monomer is developed and used to synthesize a series of polysulfamide‐based (poly (2‐((2‐(methacryloyloxy)ethyl) dimethylammonio)acetyl) (phenylsulfonyl) amide (PMEDAPA)) nanogels as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…The higher the cross-linker molar ratio used, the higher is the VPTT of the nanogels due to their more compact network structures (see Figure 2d,e). [113] Moreover, the PMEDAPA nanogels showed excellent biocompatibility and b) their UV-vis cloud points at different microgel concentrations. Reproduced with permission.…”
Section: Aqueous Precipitation Polymerizationmentioning
confidence: 95%
See 1 more Smart Citation
“…The higher the cross-linker molar ratio used, the higher is the VPTT of the nanogels due to their more compact network structures (see Figure 2d,e). [113] Moreover, the PMEDAPA nanogels showed excellent biocompatibility and b) their UV-vis cloud points at different microgel concentrations. Reproduced with permission.…”
Section: Aqueous Precipitation Polymerizationmentioning
confidence: 95%
“…Change in UCST-type VPTT of PMEDAPA nanogels d) PMEDAPA-54 and e) PMEDAPA-64; where PMEDAPA-54 and 64 stand for PMEDAPA nanogels prepared with 54 and 64 molar ratios of cross-linker, respectively. Reproduced with permission [113]. Copyright 2017, John Wiley & Sons.…”
mentioning
confidence: 99%
“…In another study, transferrin was used to enhance the tumor penetration of polysulfamide‐based (poly(2‐((2‐(methacryloyloxy)ethyl) dimethylammonio)acetyl) (phenylsulfonyl) amide) nanogels. [ 91 ] These nanogels showed a favorable penetration ability in 3D tumor spheroids.…”
Section: “Mouse Strategies” Of Surface Modification For Nanomedicine mentioning
confidence: 99%
“…In vivo studies indicated that POSS-PEG-Ce6 NPs can effectively accumulate into tumor of mice, and showed good PDT efficacy against tumor. Lu et al designed a microwave-responsive nanogel for on-demand drug delivery and enhanced cancer therapy [ 64 ]. Such nanogels were synthesized by crosslinking zwitterionic monomer (2-((2-(methacryloyloxy)ethyl) dimethylammonio)acetyl) (phenylsulfonyl) amide (MEDAPA) with ethyleneglycol dimethacrylate (EGDMA) and bis(acryloyl)cystamine (BAC).…”
Section: Crosslinked Nanogels For Cancer Diagnosis and Imaging-guimentioning
confidence: 99%